Ekosistem Pesantren dalam Mewujudkan Manajemen Halal Supply Chain Menuju Madani Society 5.0 - Suwanto, Suwanto; Gunawan, Indra (Mabny: Journal of Sharia Management and Business, 2021)
Abstract Halal supply chain management is certainly very strategic applied in the halal industry in the environment around the islamic boarding school towards madani society 5.0. This study aims to describe the principles of halal supply chain management in islamic boarding school; analyze the islamic boarding school ecosystem in realizing halal supply chain management, and explain the challenges of implementing the islamic boarding school based halal supply chain management towards madani society 5.0. This study uses a qualitative descriptive method using a hermeneutic content analysis model and the integration-interconnection approach in detail the islamic boarding school ecosystem in order to develop halal supply chain management. In general, the four principles of the halal supply chain, namely halal procurement, halal manufacturing, halal distribution, and halal logistics. The islamic boarding school ecosystem in implementing halal supply chain management certainly requires government support, transportation planning, information technology management, human resource management; collaborative relations, halal certification, and traceability of halal information. Keywords: islamic boarding school, management, halal supply chain, and madani society 5.0. Abstrak Manajemen halal supply chain tentunya sangat strategis diterapkan pada industri halal di lingkungan sekitar pesantren menuju madani society 5.0. Penelitian ini bertujuan untuk menguraikan prinsip-prinsip manajemen halal supply chain pada pesantren; menganalisis ekosistem pesantren dalam mewujudkan manajemen halal supply chain; dan menjelaskan tantangan penerapan manajemen halal supply chain berbasis pesantren menuju madani society 5.0. Penelitian ini menggunakan metode deskriptif kualitatif dengan menggunakan model content analysis hermeneutik dan pendekatan integrasi-interkoneksi menganalisis secara rinci ekosistem pesantren dalam rangka mengembangkan manajemen halal supply chain. Secara umum empat prinsip halal supply chain, yaitu halal procurement (pengadaan), halal manufacturing (pengolahan), halal distribution (distribusi), dan halal logistic (rantai pasokan). Ekosistem pesantren dalam implementasi manajemen halal supply chain tentunya membutuhkan dukungan pemerintah, perencanaan transportasi, manajemen teknologi informasi, manajemen sumber daya manusia, hubungan kolaboratif, sertifikasi halal, dan ketelusuran informasi halal. Kata kunci: pesantren, manajemen, halal suply chain, dan madani society 5.0.